Further delineation of genotype–phenotype correlation in homozygous 2p21 deletion syndromes: First description of patients without cystinuria. Issue 8 (21st June 2013) - Bartholdi, Deborah; Asadollahi, Reza; Oneda, Beatrice; Schmitt‐Mechelke, Thomas; Tonella, Paolo; Baumer, Alessandra; Rauch, Anita
ABSTRACT Homozygous contiguous gene deletion syndromes are rare. On 2p21, however, several overlapping homozygous gene deletion syndromes have been described, all presenting with cystinuria but otherwise distinct phenotypes. Hypotonia‐cystinuria syndrome (HCS, OMIM606407) is characterized by infantile hypotonia, poor feeding, and growth hormone deficiency. Affected individuals carry homozygous deletions including the cystinuria gene SLC3A1 and the adjacent PREPL gene. Larger homozygous deletions in this region encompassing the PPM1B, SLC3A1, PREPL, and C2orf34 (CAMKMT) genes result in a more severe phenotype, the 2p21 deletion syndrome. A phenotype intermediate to HCS and the 2p21 deletion syndrome is termed atypical HCS and is caused by deletion of SLC3A1, PREPL, and C2orf34 (CAMKMT). Using high resolution SNP array molecular karyotyping we identified two siblings with a homozygous deletion of 83 kb partially encompassing the genes PREPL and C2orf34 (CAMKMT), but not the SLC3A1 gene. The affected siblings display a recognizable phenotype which is similar to atypical HCS with regard to growth failure and neuro‐muscular features, but is characterized by lack of cystinuria. The patients also exhibit features which have not been reported to date such as cleft palate and genital abnormalities. In conclusion, we report the first patients with a homozygous 2p21 deletion syndrome without cystinuria and further delineate the complex genotype–phenotype correlations of homozygous microdeletion syndromes of this region. © 2013 Wiley Periodicals, Inc.